Determination of the current cost of short-term financial investments (Journal of Economic Research & Business Administration, 2016)
The article deals with the current value of short-term investments, andtheir way of analyzing and determining the price. At the present time, eachhousehold is estimated as the present valueis taken into account short-termfinancing and investment, analyzes the results of market conditions andchanges that make it possible to predict the market value. During theexecution of the investment project, discusses the changes in the presentvalue of the shares. Due to changes in commodity prices, the depreciationof investments may occur, this is shown to prevent financial project. Ininvestment projects in connection with the overvaluation of long-termfinancial investments particularly funding stops. In the course of financingthe investment amounts, you must stop in the applicable measures that donot depreciate. If the rate of your income increase, it is necessary toconsider the long-term financial investment.
Keywords: rally; share prices; dividends and currency cost; discount; investment project; the average rate of earnings; redemption; internal rate of return; pure current cost.